(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
be active functional exercise complete any physical body at a much higher level o‘- check-in passengers associated with it. So "training downloads" refers to the additional activity of the body. The activity will require a certain amount of spending power in excess of the body (this size is related to the size of the load power), this is realized the need to restore and get tired after a certain time comes to such situations to understand this article describes the wide coverage was given.